Selection of polyhydroxybutyrate-producing bacteria and their polyhydroxybutyrate production using cassava and glycerol as carbon sources - Meesilp, Nutthawut; Romsomsa, Nisa (Agriculture and Natural Resources, 2025)
Importance of the work: Polyhydroxybutyrate (PHB) produced by microorganisms has desirable properties and has been applied across various fields. However, its use in bioplastic production remains costly compared to synthetic plastics, mainly due to the expensive substrates and downstream processing. Using low cost raw materials and bacterial strains is a potential strategy to reduce production cost. Objectives: To obtain effective PHB-producing bacteria and to utilize various substrates as carbon sources for production. Materials and Methods: PHB-producing bacteria were obtained from cassava plants and their associated soil rhizosphere. Initially, all bacterial isolates were investigated qualitatively for PHB production using staining dyes and estimated quantitatively based on extraction using chloroform. Subsequently, various substrates with different concentrations were used to cultivate these bacteria for their growth and PHB production. The PHB extracts from the bacteria were investigated using gas chromatography-mass spectrometry. The effective PHB-producing bacteria were identified to the genus and species levels using 16S rRNA gene sequencing. Results: The PHB-producing bacteria isolated from the plant and soil samples had stained granules inside their vegetative cells and fluorescent colonies growing on medium under ultraviolet light. Quantitatively, the bacterial isolates CAD2 and CAD9 preliminarily cultured with glucose had higher contents of PHB extracted using chloroform than the other PHB-producing isolates. Application of various substrates to the culture isolates CAD2 and CAD9 on 1.5% (weight per volume) starch and cassava pulp produced the highest mean contents of PHB (367.75 ± 7.58 and 126.94 ± 10.35 g/L/g biomass, respectively). On the other hand, supplementation of glucose increased the number of bacteria more than it did PHB production. The isolates CAD2 and CAD9 were identified as P. aryabhattai and P. filamentosa, respectively. Main finding: Utilization of various substrates, especially cassava pulp, enhanced PHB production, including the growth of the bacteria.